2017
DOI: 10.1007/s00484-017-1494-y
|View full text |Cite
|
Sign up to set email alerts
|

Vineyard microclimate and yield under different plastic covers

Abstract: The use of plastic cover in vineyards minimizes effects of adverse weather conditions. The northwest of São Paulo State is one of the largest grape producing regions in Brazil; however, few studies investigate the effects of different plastic covers on vineyards in this region. This study compared the effect of black shading screen (BSS) and braided polypropylene film (BPF) on BRS Morena vineyard microclimate, grown on an overhead trellis system in the northwestern São Paulo. The experiments were carried out d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
1
4
0
1
Order By: Relevance
“…Overall, the plastic sheets reduced ET 0 between 27% (cover S in June) and 35% (cover C in July) in the first year and between 30% (cover S in June) and 38% (Cover C in June and July) in the second year. The range of these values is similar to that found by Cardoso et al (2008) [25]. Therefore, plastic sheet coverings can give a significant contribution to the reduction of the atmospheric evaporative demand and, therefore, to the use of the water resource required by the table grape vineyard.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Overall, the plastic sheets reduced ET 0 between 27% (cover S in June) and 35% (cover C in July) in the first year and between 30% (cover S in June) and 38% (Cover C in June and July) in the second year. The range of these values is similar to that found by Cardoso et al (2008) [25]. Therefore, plastic sheet coverings can give a significant contribution to the reduction of the atmospheric evaporative demand and, therefore, to the use of the water resource required by the table grape vineyard.…”
Section: Discussionsupporting
confidence: 82%
“…The radiometric properties of plastic screens exert a paramount influence on the microenvironment inside the structure, thus they affect evapotranspiration. Many studies refer to the influence of plastic cover on vineyard microclimate, vine physiology and grape quality [20][21][22][23][24][25][26], while a limited number of studies are focused on the effects of plastic coverings on evapotranspiration of table grape vineyards [9,[27][28][29] and, moreover, no one considers possible effects of sheets having different radiometric properties. The first aim of the present work was to estimate, in the environmental conditions of south Italy, the reference evapotranspiration that occurs during the warmest summer months under plastic sheets that cover table grape vineyards, in comparison with an open field.…”
Section: Introductionmentioning
confidence: 99%
“…This level of rainfall is not common in the region during this period and, consequently, this could be considered an atypical year (Table ). In 2014, rain fell with lower intensity and frequency (Holcman, Sentelhas, Conceição, & Couto, ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, at a given location, the prominent role exerted by plastic cover characteristics on the vine eco-physiological response should be carefully evaluated since, as revealed by covered conventional systems' experiment results, it can affect the leaf area and growth rate, the percentage of fertile buds per shoot, the number of bunches per shoot, and ultimately yields [93]. Furthermore, both the advance of berry ripening and the bunch and berry mass, are also affected, as demonstrated by Novello et al [94], who showed the better performance of 'Matilde' grapes grown under LDPE (low density polyethylene) and EVA, compared with LDPE and HDPE (high density) plastic sheet covering.…”
Section: The Covermentioning
confidence: 99%